APLIKASI PENCARIAN FASILITAS TAMBAL BAN DI KABUPATEN PRINGSEWU BERBASIS ANDROID - Irwan Adi Pribadi; Nurul Istiqomah (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
The more use of motor vehicles in Indonesia, the more increasing the need for tire patchy places. When experiencing a tire leak, the Rider will encourage the bike to find the location of the nearest tire patch. However, if the Rider has never crossed the road it will be more difficult because it has to push the bike without knowing the location of the tire patch and the operating hours of the tire patch. With the advancement of technology, smartphones are considered a necessity because they have functions that make it possible to do whatever is needed. Therefore, a Tire Patch Facility Search Application was created in Pringsewu Regency Based on Android to make it easier for Riders to know the location of tire patch and to call the Tire Patcher to the Rider's location. The application was developed using the Waterfall method which is divided into 5 stages, namely requirements analysis, system design, program code writing, testing, and maintenance. In this study, the application was built with an Android framework with program code using the Android Studio IDE and the Java programming language and Firebase Database. The results of this study show the application is able to display the location of the patchwork of the tire that is open, the application can help the Rider to call the Tire Patcher to the location, and GIS technology is successfully applied to determine the position of the Rider and the route to the location of the tire patch, and vice versa